PENGARUH BIAYA PROMOSI PENJUALAN DAN PENJUALAN PERSEORANGAN TERHADAP JUMLAH DANA DEPOSITO PADA PT. BPR SHRI GANGGA BALI CABANG KUTA - WIjayanthi, Ida Ayu Trisna; Ratini, Putu Mela; Saputra, Tri Eka (JUIMA : JURNAL ILMU MANAJEMEN, 2019)
The aims of this Research is to determine the effect of sales promotion costs and individual sales costs partially and simultaneously on the amount of deposit funds and the most dominant cost effect on the amount of deposit funds at PT. BPR Shri Gangga Bali Kuta Branch. The data analysis method used is the analysis of Multiple Linear Regression. The results of data analysis showed that the results of multiple linear regression analysis obtained by the equation Y = -4,534, + 1515,994 X1 + 120,323X2. The results of multiple linear regression analysis show that the variables of individual sales and sales promotion simultaneously affect the sale of deposit funds at PT BPR SHRI Gangga Bali, Kuta Branch. The variable that has the most dominant inï€‚uence on the amount of deposit funds is the variable of individual sales costs (X_2) because it has a Beta coefï€cient value of 1.706 compared to the coefï€cient of sales promotion costs (X_1) which is only 1.408.